Penerapan Metode Pembelajaran Cooperative Tipe Script untuk Meningkatkan Hasil Belajar PKn Siswa Kelas V di SD Negeri 008 Rambah Samo - Afrianindi Suprianti; Rejeki Rejeki (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to determine the application of the Script Type Cooperative Method in improving the learning outcomes of fifth grade students in Civics lessons. From the initial data of 20 students, 9 students achieved the KKM and 11 students did not achieve the KKM set by the school, namely 65. This type of research is classroom action research carried out in 2 cycles, consisting of planning, implementation, observation and reflection. The subjects of this study were fifth grade students of SD Negeri 008 Rambah Samo. Data collection techniques used achievement tests and observations. The research instrument used learning outcome test questions and observation sheets. The results of the study showed that before the implementation of the Script Type Cooperative method in Civics learning, 9 students had completed it while 11 students had not completed it. After the study, the learning outcomes in cycle I meeting 1 were 59.75% in cycle I meeting II increased to 61.75%, in cycle II meeting 1 obtained 73.75% and in cycle II meeting II increased to 99%. Research on the Application of the Script Type Cooperative Method to Improve Civics Learning Outcomes of Grade V Students of SD Negeri 008 Rambah Samo is said to be successful.